ANALYSIS OF KNOWLEDGE MANAGEMENT IMPLEMENTATION IN SMALL AND MEDIUM TEXTILE INDUSTRIES IN MAJALAYA, WEST JAVA - Efendi, Nur; Nurnida, Ida (Sosiohumaniora, 2024)
The competitiveness of the textile industry is determined by the implementation of knowledge management. Therefore, this research aimed to describe and analyze the implementation of knowledge management in small and medium (SMEs) textile industry in Majalaya, West Java. An exploratory descriptive design was used with an inductive approach and qualitative methods. Data collection was carried out through interviews and observations, while the analysis was conducted through stages of data reduction, display, and conclusion. The results showed that SMEs textile industry in Majalaya, West Java did not implement knowledge management optimally. There were three internal problems, namely the low skill level of the workforce, low mastery of technology, and weak learning culture. The impact of the problem was the high dependence on the knowledge of the owner and supervisor, the occurrence of hostages between the owner, supervisor, and employees, and labor practices causing companies to lose potential workforce. In this context, the implementation of knowledge management experienced obstacles, such as lack of management and leadership support, weak learning culture, low mastery of information technology, limited technological infrastructure, lack of adequate training and education practices, and human resource management practices.